Analysis Of Value Exchange Between Traditional Market Stakeholders (Case Study: Baleendah Traditional Market) - Fajar Sidiq Adi Prabowo; Radityo Priambodo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Garut, 2021)
Baleendah traditional market is one of the market located in Bandung regency. Baleendah traditional market is managed by the government of the department of cooperatives and trade. Many buyers who shop at this traditional market with the aim of selling it back because the price is quite friendly, has complete different kinds of materials and stuffs and also has a good quality that is not inferior to other shopping places. The purpose of this study is to map the exchange of values between stakeholders in the traditional market Baleendah. As well as to find out the possibility of conflict among stakeholders. Based on the analysis conducted through observation and in-depth interviews, it can be seen that the flow of value exchange that occurs among the stakeholders in the traditional market Baleendah in the form of tangible values such as money, facilities, permits, etc. also intangible values such as trust, Knowledge, suggestions or criticism and so forth. And from the identification of exchange patterns that have been made, there are stakeholders who take advantage of losses from other stakeholders.